2020
DOI: 10.3390/biomedicines8070192
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar Spindle 1 Kinase (MPS1/TTK) mRNA Expression is Associated with Earlier Development of Clinical Symptoms, Tumor Aggressiveness and Survival of Glioma Patients

Abstract: Inhibition of the protein kinase MPS1, a mitotic spindle-checkpoint regulator, reinforces the effects of multiple therapies against glioblastoma multiforme (GBM) in experimental settings. We analyzed MPS1 mRNA-expression in gliomas WHO grade II, III and in clinical subgroups of GBM. Data were obtained by qPCR analysis of tumor and healthy brain specimens and correlated with the patients’ clinical data. MPS1 was overexpressed in all gliomas on an mRNA level (ANOVA, p < 0.01) and correlated with tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our data clearly demonstrated that TXNDC5 was enriched in the tumor area of hyperplastic blood vessels and microvascular proliferation (Figure 4G,H ) which are known to contain highly proliferative cells and play a crucial role in tumor progression. 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…Our data clearly demonstrated that TXNDC5 was enriched in the tumor area of hyperplastic blood vessels and microvascular proliferation (Figure 4G,H ) which are known to contain highly proliferative cells and play a crucial role in tumor progression. 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…Expression ratio comparisons were performed using Chi-square tests, and protein expression correlation analyses were performed using Spearman's rank correlations. A P < 0.05 value indicated statistical significance [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mps1 is an attractive oncology target because of its high expression level in cancer cells and the correlation between its expression level and the histological grade of the cancer. Based on the kinase profile, the compounds selectively inhibit MPS1 and reduce the phosphorylation of MPS1 and Phospho-HH3 signaling, successfully [ 64 , 65 ].…”
Section: Pyridopyrimidines: Therapeutic Potential and Synthesismentioning
confidence: 99%